2004
DOI: 10.1029/2004jb003158
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐induced seismic anisotropy of wadsleyite polycrystals and flow patterns in the mantle transition zone

Abstract: [1] We use forward models based on recent high-pressure experimental data on mantle minerals to predict the seismic anisotropy produced by plastic strain of orthorhombic wadsleyite, the dominant mineral in the upper transition zone. These models predict a weak seismic anisotropy for a polycrystal of pyrolitic composition (60% wadsleyite, 40% garnet) at transition zone conditions: $2% for P and $1% for S waves for a shear strain of 1. Both P and S wave anisotropy patterns show an orthorhombic symmetry. P waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 48 publications
(72 reference statements)
6
58
0
2
Order By: Relevance
“…LPO of wadsleyite and/or ringwoodite could indeed explain the observed signal in the upper and lower transition zone, respectively, as they have been shown to be intrinsically anisotropic. Wadsleyite single crystal anisotropy is about 14% (Zha et al, 1997), and recent modeling showed that a polycrystal of pyrolytic composition at MTZ conditions can have ∼ 1% seismic anisotropy (Tommasi et al, 2004;Kawazoe et al, 2013), compatible with our model. The intrinsic elastic anisotropy of ringwoodite is more ambiguous.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…LPO of wadsleyite and/or ringwoodite could indeed explain the observed signal in the upper and lower transition zone, respectively, as they have been shown to be intrinsically anisotropic. Wadsleyite single crystal anisotropy is about 14% (Zha et al, 1997), and recent modeling showed that a polycrystal of pyrolytic composition at MTZ conditions can have ∼ 1% seismic anisotropy (Tommasi et al, 2004;Kawazoe et al, 2013), compatible with our model. The intrinsic elastic anisotropy of ringwoodite is more ambiguous.…”
Section: Discussionsupporting
confidence: 72%
“…According to mineral physics analyses by Tommasi et al (2004) horizontal shear has to be dominant in the MTZ in order to be compatible with radial anisotropy models showing V SH > V SV (Montagner and Kennett, 1996;Beghein et al, 2006;Panning and Romanowicz, 2006) and with V SV az-imuthal anisotropy stronger than V SH anisotropy as found by Trampert and van Heijst (2002). Models of radial anisotropy have however large uncertainties at these depths (Beghein and Trampert, 2004b;Beghein et al, 2006) and other results show V SH < V SV in the MTZ (Visser et al, 2008b).…”
Section: Discussionmentioning
confidence: 95%
“…There is some observational evidence for anisotropy in the transition zone, mainly from surface wave and normal mode observations (e.g., Trampert and van Heijst 2002;Beghein and Surv Geophys (2009) Fouch and Fischer 1996;Iidaka and Niu 1998). The development of LPO in wadsleyite, which has an intrinsic shear wave anisotropy of *13% (Mainprice 2007) has been simulated using polycrystalline plasticity modeling by Tommasi et al (2004). Overall, however, there is very little experimental data on LPO development in transition zone materials (Karato 2008).…”
Section: The Transition Zone and Lower Mantlementioning
confidence: 99%
“…Our calculated polarization anisotropy indicates that the observed polarization anisotropy can be explained by the transversely anisotropic aggregate of both dry and hydrous wadsleyite with the vertical c principal axis. Since dry and hydrous wadsleyites show relatively similar azimuthal and polarization anisotropy, the difference of the rheological properties such as crystal-preferred orientation [e.g., Tommasi et al, 2004] between dry and hydrous wadsleyite may hold the key to whether hydrous wadsleyite is detectable by assessing seismic anisotropy.…”
Section: Geophysical Implicationsmentioning
confidence: 99%